Agensia Hayati Antifungi Ekstrak Batang Faloak (Sterculia quadrifida R.Br.) terhadap Fusarium oxysporum - Asmiati Asmiati; Yampianus Linome; Ernawati Ernawati (Program Studi Pendidikan Biologi, FKIP, Universitas Nusa Nipa, 2026)
Fusarium oxysporum is one of the fungi that cause diseases in plants, which can result in losses for farmers. Efforts to control fungi using synthetic fungicides can lead to pathogen resistance, environmental pollution, and even poisoning in humans. Therefore, the search for new sources of natural fungicides is considered necessary because they are safer and pose minimal risk.This study aims to determine the activity of faloak stem extract (Sterculia quadrifida R.Br.) as a fungicidal biological agency in inhibiting the growth of Fusarium oxysporum. This research has been carried out at the Biology Laboratory, Muhammadiyah University of Kupang. This study is a laboratory experimental study with 4 treatments and 4 repeats, namely A as a control, B = 0.5 ml, C = 0.75 ml, and D = 1 ml. The parameter measured was the diameter of the colony of F.oxysporium during 5 days of incubation. Colony diameter data were analyzed with Anova and further tested with Duncan. The research results showed that the lowest average colony diameter was obtained from treatment D, measuring 1.01 cm, with very strong antifungal activity. Meanwhile, fungal colony growth in the control medium reached 8.5 cm, indicating no antifungal activity. Further analysis revealed that each treatment was significantly different. This indicates that faloak stem extract is capable of inhibiting the growth of F. oxysporum, and it can therefore be concluded that faloak stem extract has potential as a biological fungicidal agent against Fusarium oxysporum.